Theoretical review for leadership and employee retention in civil aviation authority sector - ELBAHRI, FAISEL MOHAMED; AZAM, S. M. FERDOUS; THAM, JACQULINE (International Journal of Multidisciplinary Research and Studies, 2023)
As workplaces adapt to meet the competing needs of different generations, so must talent management as a concept. It is no longer sufficient to have a workforce that says, stays, and works hard. Firms must consider workforce sustainability; ensure that our workplaces are representative of the larger marketplace profile and that these diverse views, experiences, and skills are respected and considered; and have confidence that employees are motivated and empowered to think creatively and constantly seek new and better ways of working. Using literature review, this study tried to highlight the theories pertaining the leadership and employee’s retention in the aviation sector. Findings expressed that employees must perform well, emphasizing the crucial importance of performance management in retaining top talent. In this context, the issue of applying the best leadership strategy and style to support and encourage such performance management initiatives arises. Continuous performance management planning and implementation will also assist management in analyzing all workers' contributions to the organization's success. Employee retention requires a continuous process of objective setting for organizational operational development, assessing progress, and providing employees with opportunities for effective coaching and feedback to assist them in meeting their career goals and objectives.